Analysis of tunable characteristics of liquid-crystal-based hyperbolic metamaterials. Issue 12 (25th September 2016) - Cao, Zhaoliang; Xiang, Xiangjun; Yang, Chengliang; Zhang, Ying; Peng, Zenghui; Xuan, Li
ABSTRACT: We propose a voltage-tunable hyperbolic dispersion metamaterial (HDM) consisting of silver nanowires and nematic liquid crystals (NLCs). The metamaterial shows a novel electro-optic effect, in which the dispersion relation switches between elliptic and hyperbolic dispersions at the visible waveband with an external electric field. HDM functionality is analysed in detail based on the effective medium theory. 5CB NLC is chosen for the simulation, and tunability is achieved between 454 and 475 nm. The effects of filling ratio on tunability are also analysed. Tunable bandwidth widens from 21 to 45 nm with decreased filling ratio from 0.27 to 0.09. Finally, the effects of birefringence (Δ n ) are considered. Tunable bandwidth widens from 21 to 63 nm as Δ n changes from 0.2 to 0.6. These novel tunable performances of the HDM can be applied to optical devices and optical systems. GRAPHICAL ABSTRACT: